2023
DOI: 10.1097/gox.0000000000004869
|View full text |Cite
|
Sign up to set email alerts
|

Early Simultaneous Cross Facial Nerve Graft and Masseteric Nerve Transfer for Facial Paralysis after Tumor Resection

Abstract: Background: We describe a new approach for facial reanimation after skull base tumor resection with known facial nerve sacrifice, involving simultaneous masseter nerve transfer with selective cross facial nerve grafting (CFNG) within days after tumor surgery. This preliminary study compared outcomes of this approach versus a staged procedure involving a masseter nerve “babysitter” performed in a delayed timeline. Methods: Patients undergoing masseter nerve transfer and CFNG for facial paralysis after skull b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As such, CFNG is usually only considered as a single-stage procedure within 6 months from the time of facial nerve injury. It is important to note, however, that the limited donor axons may achieve somewhat unpredictable results as a single-stage procedure, and as such even in cases of limited facial injury and denervation of less than 6 months, CFNGs may be placed at the same time as an ipsilateral motor nerve transfer, such as the masseteric nerve, to provide more reliable axonal delivery and improve resting facial tone and oral commissure excursion [27,28]. In patients with denervation time of greater than 6 months, a two-stage procedure is required whereby the first stage involves using an ipsilateral motor donor to provide strong innervation to salvage the facial musculature while the CFNGs are growing across the face.…”
Section: Cross Facial Nerve Graftmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, CFNG is usually only considered as a single-stage procedure within 6 months from the time of facial nerve injury. It is important to note, however, that the limited donor axons may achieve somewhat unpredictable results as a single-stage procedure, and as such even in cases of limited facial injury and denervation of less than 6 months, CFNGs may be placed at the same time as an ipsilateral motor nerve transfer, such as the masseteric nerve, to provide more reliable axonal delivery and improve resting facial tone and oral commissure excursion [27,28]. In patients with denervation time of greater than 6 months, a two-stage procedure is required whereby the first stage involves using an ipsilateral motor donor to provide strong innervation to salvage the facial musculature while the CFNGs are growing across the face.…”
Section: Cross Facial Nerve Graftmentioning
confidence: 99%
“…Clinical outcomes were good to excellent, with voluntary contraction observed after 2–4 months, and spontaneous contraction was achieved in 7–13 months postoperatively. Sergesketter et al [28] studied patients who had skull base tumor resection and known facial nerve sacrifice, and compared simultaneous masseter nerve transfer with selective CFNG within days from their skull base surgery, with a staged procedure involving the masseter nerve as a ‘babysitter’ and CFNG. They found that the early technique appeared to result in similar clinician-reported and patient-reported outcomes compared with the delayed procedure, although synkinesis was higher in the earlier approach group.…”
Section: Masseter Nerve Transfermentioning
confidence: 99%